Revitalisasi Laboratorium IPA SMA Negeri 14 Ambon sebagai Media Pembelajaran Kimia Interaktif dan Kontekstual: Revitalization of the Science Laboratory at SMA Negeri 14 Ambon as an Interactive and Contextual Chemistry Learning Medium - Manuhutu, Julita B.; Mariwy, Abraham; Tahya, Dominggus; Fadli, Muhamad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The science laboratory plays an important role in supporting meaningful chemistry learning because it allows students to conduct observations and experiments and to develop scientific process skills. However, the science laboratory at SMA Negeri 14 Ambon has not been utilized optimally due to limited facilities, lack of maintenance, and minimal integration of interactive and contextual learning media. This community service activity aims to revitalize the science laboratory through simple chemistry demonstrations, teacher and laboratory staff training, and the provision of basic practicum equipment. The program involved 50 tenth- and eleventh-grade students and 13 teachers/laboratory staff. The initial test results before the chemistry demonstration showed that only 5 students (10%) achieved the "good" category, 10 students (20%) reached the "fair" category, while 35 students (70%) fell into the "poor" category, and none achieved the "very good" category. After the chemistry demonstration, there was a significant improvement in student understanding: 10 students (20%) reached the "very good" category, 25 students (50%) reached the "good" category, and none reached the "poor" category. Teachers and laboratory staff also experienced increased competencies: the ability to design practicum activities rose from 46% to 88%, laboratory administration from 40% to 84%, and laboratory safety management from 35% to 82%. Thus, revitalizing the science laboratory can significantly improve the quality of chemistry learning.